MOTIVASI SANTRI MENGHAFAL HADITS DI PESANTREN AL FATAH TEMBORO MAGETAN - Phila Delphia; Maskuri Bakri; Fita Mustafida (VICRATINA, 2021)
This article explains how student are able to memorize thousands of hadiths and turn them into a tradition. This study uses qualitative research through a phenomenological approach to understand the phenomenon, especially the attitudes and experiences of the Islamic boarding school community related to the research and memorization of hadith. In collecting data, this research uses interviews, observation, and documentation. Interviews were used to collect data about the process, and objectives of memorizing hadith at the Al-Fatah Islamic boarding school, Temboro, Magetan, East Java. Interviews were conducted with teachers, and students involved in the hadith memorization program. Observations were made by observing directly in the learning process of hadith studies including memorizing hadith. Then the documentation is used to collect data and documents related to the memorization of the hadith. This findings show how enthusiastic the students are in memorizing and how the teachers continue to motivate the students to remain consistent in memorizing. With this memorization policy, scientific traditions can be maintained and a strong religious atmosphere can be created, both in the environment and even when students return home. This is in accordance with the goals of the vision and mission of the boarding school, teachers and parents of students. Kata Kunci: Motivation, Students, Memorize, Hadith